Correlation of electrical resistivity and groundwater arsenic concentration, Nawalparasi, Nepal (Journal of Nepal Geological Society, 2004)
The Asian Arsenic Crisis has expanded into the headwaters of the Ganges River, now including the plains (Terai) of Nepal. This study seeks a non-invasive predictive tool to estimate groundwater arsenic concentration prior to drilling, enabling "arsenic avoidance" in contaminated areas. Detailed chemical studies indicate that in Himalayan-sourced aquifers arsenic is released by microbially-mediated redox reactions. Likely hydrogeological settings for oxidizing chemical conditions (immobile arsenic) should be more porous (higher in filtration rate for oxygenated waters) and contain fewer fine organic sediments (oxygen-consuming material). Both conditions should yield higher electrical resistivity, and such aquifer heterogeneity effects should be most prominent in head water regions such as Nepal. To test this approach, a series of vertical electrical resistivity soundings were made near Parasi, Nepal, constituting a profile extending 2 km across a known high-arsenic area. Correlation of the horizontal and vertical distribution of measured resistivity and ENPHO groundwater arsenic measurements demonstrated a distinct inverse relationship between these variables. Out of 240 arsenic sample points, 75% of those extracted from high resistivity zones (>100 ohm-m, inferred lower clay content) exhibited arsenic 150 ppb. Given these preliminary results, the resistivity technique appears to hold great promise as a predictive tool for finding low-arsenic groundwater zones within contaminated areas, thereby allowing "well-switching" from highly toxic to new safe or more readily treatable wells. The method should be applicable in most circum- Himalayan high-arsenic areas.